ISOTOPE ANALYSIS AS A MEANS OF TRACING AQUATIC PRODUCTS AUTHENTICITY, SOURCE AND GEOGRAPHIC ORIGINS - TRUONGHUYNH, H.T.; LI, G.B.; JAGANATHAN, G.K. (Italian Journal of Food Science, 2020)
Aquatic products provide good sources of high-quality protein for humans. Tracing the origin of aquatic products is of critical importance both for consumers and suppliers. In recent years, isotope analysis is becoming a key instrument in food products authentication. This work reviews the use of isotope analysis to trace the production sources (wild or farmed) and geographic origins of aquatic products. Extensive research has studied the isotope values of freshwater fish to Atlantic salmon, sea bass, rainbow trout, and other commercial fish and shellfish. Generally, the ratios of carbon (?13C) and nitrogen (?15N) stable isotopes were successfully investigated in aquatic products in order to identify the production methods or geographic origins. However, the predictable confidence of isotope analysis can be enhanced in combination with other analytical techniques, such as fatty acids and multi-element profiling. Moreover, future research to combine isotope analysis with data fusion and multivariate data evaluation is recommended.